2009
DOI: 10.1016/j.nurt.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Brain Stimulation Protocols in the Treatment of Epilepsy: Current State and Perspectives

Abstract: Summary:In epileptic seizures, there is an enhanced probability of neuronal networks to fire synchronously at high frequency, initiated by a paroxysmal depolarisation shift. Reducing neuronal excitability is a common target of antiepileptic therapies. Beyond or in addition to pharmacological interventions, excitability-reducing brain stimulation is pursued as an alternative therapeutic approach. Hereby, noninvasive brain stimulation tools, such as transcranial magnetic stimulation (TMS) and transcranial direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
86
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 53 publications
0
86
0
3
Order By: Relevance
“…However, the poor correlation between real seizure frequency and those reported by patients makes the boundary of a possible placebo effect difficult to find. 5 There is also increasing evidence that transcranial stimulation might improve selective skills in cognitive disorders such as Alzheimer disease. These findings are very preliminary, since improving performances in a single task does not necessarily represent a global cognitive enhancement.…”
mentioning
confidence: 99%
“…However, the poor correlation between real seizure frequency and those reported by patients makes the boundary of a possible placebo effect difficult to find. 5 There is also increasing evidence that transcranial stimulation might improve selective skills in cognitive disorders such as Alzheimer disease. These findings are very preliminary, since improving performances in a single task does not necessarily represent a global cognitive enhancement.…”
mentioning
confidence: 99%
“…A repetitive protocol in which one session of tDCS is applied daily over the course of several days or weeks may prolong these effects even longer. The optimal protocol for tDCS has yet to be established, with important questions regarding optimal stimulation duration, repetition rate, reference electrode position, and stimulation strength still unanswered (Nitsche and Paulus, 2009). …”
Section: Transcranial Direct-current Stimulation (Tdcs)mentioning
confidence: 99%
“…The coil delivers the magnetic current through the skull which induces an electric current in the brain that elicits action potentials in cortical neurons approximately 1.5-2.0 cm beneath the scalp (Epstein et al, 1990). Animal studies showed that if the electrical current repetitively activated these cortical neurons, long-lasting changes in cortical excitability will have occurred, leading to the discovery of rTMS (Nitsche and Paulus, 2009). The type of excitability change is determined by the frequency of the repeated pulses, such that low-frequency rTMS (≤ 1 Hz) reduces cortical excitability and high-frequency rTMS (> 1 Hz) increases cortical excitability (Pascual-Leone et al, 1998) but these changes are not necessarily synonymous with increased inhibition or excitability, respectively.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…Tidlige faser av kliniske studier har vist at behandlingen potensielt kan brukes ved epilepsi (19,20), alvorlig depresjon (21,22) og rusavhengighet (23)(24)(25). I tillegg kan stimuleringen fasilitere motorisk funksjon etter hjerneslag (26,27) og hukommelsesfunksjon ved Alzheimers sykdom (28).…”
unclassified